RANCANG BANGUN SISTEM KENDALI LAMPU OTOMATIS BERBASIS INTERNET OF THINGS (IOT) - Zaskia Gusvalia; Amru Yasir; Ahir Yugo Nugroho (Universitas Dharmawangsa, 2026)
The rapid development of Internet of Things (IoT) technology has created significant opportunities in home automation, particularly in lighting systems. This research aims to design and implement an automatic lamp control system based on IoT, which can be operated via smartphone using the Blynk application. The system employs an ESP32 microcontroller as the central controller, a Light Dependent Resistor (LDR) sensor to detect light intensity, and an ACS712 current sensor to measure electrical consumption. A relay module is used to switch the lamp on or off according to commands from the ESP32, enabling both manual and automatic control depending on environmental conditions. The research methodology includes literature review, observation of conventional lighting systems, and direct experimentation through hardware and software design. The results show that the system successfully adjusts lighting automatically based on ambient light intensity while also providing real-time energy consumption data through the Blynk application. Therefore, this system not only improves energy efficiency but also enhances convenience, safety, and user comfort in controlling household lighting remotely.